Smoking related COPD and facial wrinkling: is there a common susceptibility? - Patel, B D (BMJ Group, 2006)
BACKGROUND: Cigarette smoking causes accelerated facial wrinkling and predisposes to chronic obstructive pulmonary disease (COPD). However, it has long been recognised that there is a subgroup of susceptible smokers who are at increased risk of developing airflow obstruction. We have tested the hypothesis that there is a common susceptibility for the development of COPD and facial wrinkling in cigarette smokers. METHODS: One hundred and forty nine current and ex‐smokers were recruited from a family based study of COPD genetics, 68 (45.6%) of whom fulfilled the definition of COPD. 124 (83.2%) had no or minor facial wrinkling (Daniell <IV) and 25 (16.8%) were wrinkled (Daniell score ⩾IV). Generalised estimating equations were used to adjust for familial correlations between related individuals and the potential confounding effects of age and pack years smoked. RESULTS: Forced expiratory volume in 1 second (FEV(1)) was significantly lower in those with wrinkles than in those without (mean difference in FEV(1) % predicted −13.7%, 95% CI −27.5 to 0.0, p = 0.05) and facial wrinkling was associated with a substantially increased risk of COPD (adjusted OR 5.0, 95% CI 1.3 to 18.5, p<0.02). The Daniell score correlated with the extent of emphysema on the CT scan (p<0.05) and facial wrinkling was also associated with a greater risk of more extensive emphysema (adjusted OR 3.0, 95% CI 1.0 to 9.3, p = 0.05). CONCLUSION: Facial wrinkling is associated with COPD in smokers, and both disease processes may share a common susceptibility. Facial wrinkling in smokers may therefore be a biomarker of susceptibility to COPD.